Blinatumomab and inotuzumab for B cell precursor acute lymphoblastic leukaemia in children: a retrospective study from the Leukemia Working Group of the Spanish Society of Pediatric Hematology and Oncology (SEHOP). (21st April 2020) - Fuster, José L.; Molinos‐Quintana, Agueda; Fuentes, Carolina; Fernández, José M.; Velasco, Pablo; Pascual, Toñi; Rives, Susana; Dapena, José L.; Sisinni, Luisa; López‐Godino, Oriana; Palomo, Pilar; Villa‐Alcázar, Marta; et al.
Summary: Blinatumomab and inotuzumab ozogamycin represent promising alternatives to conventional chemotherapy in acute lymphoblastic leukaemia (ALL). We analysed data from 29 children with ALL treated under compassionate use with blinatumomab, inotuzumab or both. The complete remission (CR) rate in a heavily pretreated population with overt relapse was 47·6%. At earlier stages (first/second CR), both antibodies represented a useful tool to reduce minimal residual disease, and/or avoid further toxic chemotherapy until stem cell transplantation. Six patients developed grade 3 reversible non‐haematological toxicity. The 12‐month overall survival and event‐free survival rates were 50·8 ± 26·4% and 38·9 ± 25·3% with blinatumomab, 45·8 ± 26% and 27·5 ± 25% with inotuzumab.